A capacitor overvoltage elimination strategy for reduced-voltage-sensor-based MMC. (November 2021) - He, Ruizhi; Jin, Yu; Hou, Weiyang; Luo, Derong; Huang, Shoudao
Abstract: As modular multilevel converter(MMC) requires a large number of sensors to measure capacitor voltages, reducing the number of sensors for MMC has become an emerging topic. One of the technical challenges for reduced-voltage-sensor-based MMC operated with NLM is to eliminate the overvoltage that occurred on submodules. In order to solve this problem, a capacitor overvoltage elimination strategy for reduced-voltage-sensor-based MMC is proposed in this paper. The overvoltage elimination is consists of pre-measurement and in-process measurement of capacitor voltage, which is to obtain the actual value of submodule capacitor voltage so that to sort submodule capacitor voltages in the correct sequence. In this way, the submodules with excessively high voltage or with overvoltage trends can be selected for discharging until their voltages reach the normal level. Therefore, the overvoltage that occurred on submodules can be eliminated. A 31-level single-phase MMC simulation model is performed in MATLAB/SIMULINK, and a 9-level one is constructed in an experimental laboratory. Both the simulation and experimental results verify the effectiveness of the proposal even in the situation of capacitance parameter deviation.